C5a-C5aR1 Axis Activation Drives Envenomation Immunopathology by the Snake Naja annulifera - Silva de França, Felipe; Villas-Boas, Isadora Maria; Cogliati, Bruno; Woodruff, Trent M.; Reis, Edimara da Silva; Lambris, John D.; Tambourgi, Denise V. (Frontiers in Immunology, 2021)
Systemic complement activation drives a plethora of pathological conditions, but its role in snake envenoming remains obscure. Here, we explored complement’s contribution to the physiopathogenesis of Naja annulifera envenomation. We found that N. annulifera venom promoted the generation of C3a, C4a, C5a, and the soluble Terminal Complement Complex (sTCC) mediated by the action of snake venom metalloproteinases. N. annulifera venom also induced the release of lipid mediators and chemokines in a human whole-blood model. This release was complement-mediated, since C3/C3b and C5a Receptor 1 (C5aR1) inhibition mitigated the effects. In an experimental BALB/c mouse model of envenomation, N. annulifera venom promoted lipid mediator and chemokine production, neutrophil influx, and swelling at the injection site in a C5a-C5aR1 axis-dependent manner. N. annulifera venom induced systemic complementopathy and increased interleukin and chemokine production, leukocytosis, and acute lung injury (ALI). Inhibition of C5aR1 with the cyclic peptide antagonist PMX205 rescued mice from these systemic reactions and abrogated ALI development. These data reveal hitherto unrecognized roles for complement in envenomation physiopathogenesis, making complement an interesting therapeutic target in envenomation by N. annulifera and possibly by other snake venoms.